The octopus scientists : exploring the mind of a mollusk - Montgomery, Sy (Scientists in the field., 2015)
Looks at the work of renowned octopus scientist Jennifer Mather and a team of researchers on the island of Moorea, near Tahiti in the South Pacific, where they work to learn more about octopuses and their behavior.